THE ELEMENTS OF SUCCESSFUL SUPPLY CHAIN COLLABORATION: INTERRELATIONSHIPS, ENABLERS AND INHIBITORS - Avornyo-Keledorme, Praise (2014)
Purpose: The purpose of this research is to identify the interrelationships between elements of supply chain collaboration to inform management action and also outline enablers and inhibitors that they need to focus on to have successful collaborative relationships. Design/methodology: The research is based on a case study company in the manufacturing industry where collaborative relationships are relatively advanced. Semi-structured interviews are used to collect data from two senior managers of the case study company. The analysis was done using the interview summaries and Soft Systems Methodology approach applied to model the interrelationships between the elements. Findings: The identified elements were found to have varying importance depending on the stage of collaboration. A matrix of the relative importance of the elements from the start of collaboration to a developed relationship was created. Attention was also drawn to two additional elements; collaboration management and capability, which are rarely identified in the literature as elements. Direct and indirect relationships between some of the elements were established and modelled using SSM approach to show their dependencies. The enablers and inhibitors of collaboration at the strategic and operational levels were outlined, providing management relevant information on what to focus on to have successful collaborative relationships. The objectives of the research were therefore met. Originality: The application of the SSM approach to outline the interdependencies between the elements of collaboration is novel and can be regarded as a pilot case study to encourage further research that could provide more compelling outcomes.